AlGaN/GaN metal–oxide–semiconductor high-electron-mobility transistors with a high breakdown voltage of 1400 V and a complementary metal–oxide–semiconductor compatible gold-free process - Liu, Xinke (2013)
This paper reports the fabrication and characterization of AlGaN/GaN-on-sapphire metal–oxide–semiconductor high-electron-mobility transistors (MOS-HEMTs) using a complementary metal–oxide–semiconductor (CMOS) compatible gold-free process. Devices with a gate-to-drain spacing LGD of 20 m achieved an off-state breakdown voltage VBR of 1400 V and an on-state resistance Ron of 22m cm2. This is the highest VBR achieved so far for gold-free AlGaN/GaN MOS-HEMTs. In addition, high on/off current ratio Ion=Ioff of 109 and low gate leakage current IG of 10 11 A/mm were also obtained.